Force sensorless admittance control of body weight support system. (3rd April 2021) - Huo, Jun; Huang, Jian; Tu, Xikai; Fu, Zhongzheng
Abstract : The effectiveness of rehabilitation treatment with the Body Weight Support (BWS) system has been demonstrated in patients with stroke and spinal cord injury. Many recent studies used expensive force sensors to realize the force control, which plays an important role in a BWS system. To reduce the system cost and complexity, and overcome some shortcomings of force sensors like measurement noise and lag, a force sensorless admittance control method is proposed. Then, an active BWS platform has been designed to verify the effect of the sensorless control method. The robust stability of the BWS system was proved through the small gain theorem. Human walking experiments assisted by the BWS system were conducted. It turns out that the estimated force is in close agreement with the value measured by the force sensor. The proposed controller achieved a control deviation of less than 10% around a desired mass offload during the experiments. It was validated effective for the proposed controller in accurate force control. GRAPHICAL ABSTRACT: